Sunday Painting dan Storytelling: Memperkenalkan Public Speaking kepada Anak Panti Asuhan Al-Hayat - Nurhadi, Zikri Fachrul; Ain Naya, Pramedistiyani Noer; Soraya, Adinda; Salamah, Ummu (Universitas Garut, 2024)
Abstract Public speaking training through Sunday painting and storytelling activities at the Panti Asuhan Al-Hayat was successfully implemented using a systematic method. The activity began with initial observations to understand the condition of the underwear and the children's needs. Orientation is carried out through painting and storytelling activities, testing children's confidence in speaking in front of friends. The material is presented in age-appropriate language, covering the basics of public speaking, techniques and benefits. Practices are carried out to implement the material, exploring children's courage to speak in public. Evaluation involves questions and open discussion to assess the effectiveness of the program. The activity ended with public speaking practice, where children were given the opportunity to become MCs, presenters or storytellers. Evaluation is carried out with questions and discussions to see progress. This program aims to develop children's potential, increase self-confidence, and practice public speaking skills. This ability is invaluable in everyday life and various professional fields. The results of the practice showed increased self-confidence, although some still felt shy. Factors such as past experiences and fears do not affect their performance. Prizes are given as a form of appreciation and motivation. This public speaking training provides a good foundation for children to develop valuable communication skills in facing various situations in the future. This program not only provides practical benefits, but also motivates children to overcome shyness and build the confidence needed in public speaking. Keywords: Public speaking; sunday painting; storytelling. Abstrak Pelatihan public speaking melalui kegiatan Sunday painting dan Storytelling di Panti Asuhan Al-Hayat sukses dilaksanakan dengan metode yang sistematis. Kegiatan dimulai dengan observasi awal untuk memahami kondisi panti dan kebutuhan anakanak. Program ini bertujuan mengembangkan potensi anak-anak, meningkatkan rasa percaya diri, dan melatih keterampilan public speaking. Kemampuan ini sangat berharga dalam kehidupan sehari-hari dan berbagai bidang profesional. Orientasi dilakukan melalui kegiatan painting dan storytelling, menguji kepercayaan diri anak-anak dalam berbicara di depan teman-teman. Materi disampaikan dengan bahasa yang sesuai usia, mencakup dasar-dasar public speaking, teknik, dan manfaatnya. Praktik dilakukan untuk mengimplementasikan materi, mengasah keberanian anak-anak untuk berbicara di depan umum. Evaluasi melibatkan pertanyaan dan diskusi terbuka untuk menilai efektivitas program. Kegiatan diakhiri dengan praktik public speaking, dimana anak-anak diberi kesempatan sebagai MC, presenter, atau pendongeng. Evaluasi dilakukan dengan pertanyaan dan diskusi untuk melihat kemajuan. Hasil praktik menunjukkan peningkatan kepercayaan diri, walaupun beberapa masih merasa malu. Faktor seperti pengalaman masa lalu dan ketakutan yang tidak realistis mempengaruhi performa mereka. Hadiah diberikan sebagai bentuk apresiasi dan motivasi. Pelatihan public speaking ini memberikan dasar yang baik bagi anak-anak untuk mengembangkan keterampilan komunikasi yang berharga dalam menghadapi berbagai situasi di masa depan. Program ini tidak hanya memberikan manfaat praktis, tetapi juga memotivasi anak-anak untuk mengatasi rasa malu dan membangun kepercayaan diri yang diperlukan dalam berbicara di depan umum.Kata-kata kunci: Public speaking; sunday painting, storytelling.